Rates of hypogonadism forms in Klinefelter patients undergoing testicular sperm extraction: A multicenter cross‐sectional study. (3rd July 2020) - Pozzi, Edoardo; Boeri, Luca; Capogrosso, Paolo; Palmisano, Franco; Preto, Mirko; Sibona, Mattia; Franceschelli, Alessandro; Ruiz‐Castañé, Eduard; Sarquella‐Geli, Joaquim; Bassas‐Arnau, Lluís; Scroppo, Fabrizio I.; Gentile, Giorgio; et al.
Abstract: Introduction and objectives: Adult patients with Klinefelter syndrome (KS) may present with testicular volume loss and a decrease in circulating testosterone (T) levels. However, the actual rate of hypogonadism in adult KS men is unknown. We aimed to (a) assess the prevalence of different forms of hypogonadism in a cohort of KS patients with non‐obstructive azoospermia (NOA); and (b) investigate potential preoperative predictor of positive sperm retrieval (SR) at surgery in the same cohort of men. Methods: Complete data from 103 KS men with NOA who underwent testicular sperm extraction (TESE) between 2008 and 2019 at five centers were analyzed. Comorbidities were scored with the Charlson Comorbidity Index (CCI). Patients were categorized into four groups of hypogonadism as follows: eugonadism [normal total T (tT) (≥3.03 ng/mL) and normal luteinizing hormone (LH) (≤9.4 mUI/mL)], secondary hypogonadism [low tT (≤3.03 ng/mL) and low/normal LH (≤9.4 mUI/mL)], primary hypogonadism [low tT (≤3.03 ng/mL) and elevated LH (≥9.4 mUI/mL)], and compensated hypogonadism [normal tT (≥3.03 ng/mL) and elevated LH (≥9.4 mUI/mL)]. Descriptive statistics tested the association between clinical characteristics and laboratory values among the four groups. Results: Median (IQR) patients age was 32 (24, 37) years. Baseline follicle‐stimulating hormone and tT levels were 29.5 (19.9, 40.9) mUI/mL and 3.8 (2.5, 11.0) ng/mL, respectively. Eugonadism, primary hypogonadism, and compensated hypogonadism were found in 16 (15.6%), 34 (33.0%), and 53 (51.4%) men, respectively. No patients had secondary hypogonadism. Positive SR rate at TESE was 21.4% (22 patients); of 22, 15 (68.2%) patients underwent assisted reproductive technology and five (22.7%) ended in live birth children. Patients' age, BMI, CCI, FSH levels, and positive SR rates were comparable among hypogonadism groups. No preoperative parameters were associated with positive SR at logistic regressions analysis. Conclusions: Findings from this cross‐sectional study showed that 15.6% of adult KS men have normal tT values at presentation in the real‐life setting. Most KS patients presented with either compensated or primary hypogonadism. Sperm retrieval rates were not associated with different forms of hypogonadism.